Ascorbic Acid Degradation in Cut Lemon Packaged Using Oxygen Scavenging Active Film During Storage - Yuniarto, Kurniawan; Purwanto, Setyo; Welt, Bruce Ari; Lastriyanto, Anang (UI Scholars Hub, 2018)
Oxygen scavenging active film can be used to prevent diffusion of free oxygen due to the action of permeation mechanism. In this study, biodegradable oxygen scavenging plastic film was designed by incorporating an antioxidant agent into plasticized polylactic acid or PLA-PEG (PPLA). Butylated hydroxytoluene (BHT) was added at different concentrations into the matrix of the PPLA film using a direct casting method to produce oxygen scavenging active film. The antiradical activity of the oxygen scavenging active film was observed, which could be applied for preventing vitamin C degradation in cut lemon during storage. The antiradical activity of the active film composite reduced after 4 days of storage at 28 °C. Initial antiradical activities were measured at 99.90%–99.91% after introducing 1%, 5%, and 10% concentrations of BHT into the matrix of the PPLA film. DPPH analysis indicated that a larger concentration of BHT exhibited higher antiradical activity after 4 days of storage surrounded with free oxygen. The final antiradical activities were 35.45%, 54.56%, and 81.65% at 1%, 5%, and 10% BHT concentrations, respectively. Therefore, incorporating a higher BHT fraction into the oxygen scavenging active film composite can certainly prevent the oxidation of cut lemon. The respective final vitamin C levels were 13.5%, 20.6%, and 22.5% after 4 days of storage.